DEVELOPMENT OF POWERS RELATED TO MANAGEMENT ACTIVITIES (Educator Insights: Journal of Teaching Theory and Practice, 2025)
ThiIn today’s dynamic and competitive business environment, the importance of developing management competencies cannot be overstated. This paper examines the importance of developing management competencies and emphasizes a holistic approach that integrates the knowledge, skills, and attitudes necessary for effective leadership. Through a comprehensive review of the relevant literature and practical insights, this paper aims to provide a roadmap for individuals and organizations seeking to enhance their management capabilities and achieve sustainable success.s article presents a linguistic analysis of the poetic works of Abdulla Oripov—one of the most prominent figures in modern Uzbek literature. Special attention is given to the application of linguistic elements in his poetry, their aesthetic and stylistic weight, and the harmony between poetic syntax and artistic expression. The paper examines Oripov’s unique poetic style, his rich lexical resources, his strategic use of grammatical tools, and the expressive power of linguistic devices within the poetic structure. These aspects are analyzed in light of both theoretical linguistics and literary stylistics.